Association of soluble HLA-G and HLA-G 14bp ins /del Polymorphism in some Iraqi patients with Breast Cancer - Hanaa N. Abdullah1 , Alia Gh. Abdulwahid2 (Indian Journal of Forensic Medicine & Toxicology, 2020)
Human leukocyte antigen-G is known to be implicated in a tumor-driven immune escape mechanism in malignancies. The main objective of the study is to evaluate the HLA-G 14-bp polymorphism in the 3?- untranslated region of the HLA-G gene in that associated with the susceptibility to breast cancer patients. This study has been done on 60 BC patients & 30 Benign tumor and30 control groups. Estimation of sHLA-G markers was assayed by using ELISA technique. Thus, polymorphism of HLAG HLA-G 14-bp were detected by PCR methods. The plasma levels of HLA-G shows a significant elevation in BC patients compared to benign breast tumour and controls (32.79±0.9vs. 13.84 ±0.30 and 12.72 ±0.45 ng/ml, P?0.05). There was a significant difference between newly diagnosed breast cancer patients and healthy control groups in homozygous genotype HLA-G 14-bp del/del genotyping (66.7% vs. 36.7%; OR=3.45; P?0.01). While, no significant differences in the homozygous genotypes Ins/ins frequency were observed between patients with breast cancer (6.6%) and the healthy control group (0.0%) (OR=3.45, P?0.001). There was a significant increase frequency of heterozygous genotype Ins/del in controls compared to patients (63.3%vs.26.7%). No significant difference was found between the patients and control groups at HLA-G 14bp insertion and deletion allelic frequency.